The effectiveness of patient safety training in increasing nurses' motivation at the Bangkinang Regional General Hospital, Kampar Regency, Riau Province - Hidayat, Ridha; Kasumayanti, Erma; Fahmi, Muhammad Muzakir; Gutama, Rozitri (Universitas Aisyah Pringsewu, 2024)
Patient safety is a critical component of healthcare services. According to the World Health Organization (WHO, 2020), approximately 10% of patients worldwide experience adverse events during hospital care. In Indonesia, the challenge of improving patient safety remains prominent, particularly in resource-limited hospitals. Training on patient safety is expected to enhance nurses’ knowledge, skills, and motivation, which in turn can improve service quality. This study aimed to assess the effectiveness of patient safety training in increasing nurse motivation at Bangkinang Regional General Hospital. A quantitative pre-test–post-test design was used with a sample of 100 randomly selected nurses. The training was conducted over two days, from February 12 to 13, 2024. The results revealed a statistically significant improvement in nurses’ work motivation following the training. These findings highlight the importance of structured patient safety programs as part of continuous professional development to foster a culture of safety and enhance the quality of care